2017
DOI: 10.1177/1012690217725906
|View full text |Cite
|
Sign up to set email alerts
|

Trying to fit in – Upper secondary school students’ negotiation processes between sports culture and youth culture

Abstract: In this paper we present results concerning how students in a Danish upper secondary school negotiate between sports culture and the prevailing norms of youth culture in a local school context. The study shows that it can be rather difficult for young people to combine sports culture with the local youth culture, because living a healthy and physically active life doesn’t fit very well with the prevailing norms of youth culture, which involve a dominant social arena characterized by parties and alcohol. By app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, Stine et al developed a study on the coupling of physical culture and youth culture using Danish high school students as an example and pointed out that traditional physical culture is difficult to subtly integrate into youth culture [15]. Bocketti explored the role of the spread of sports culture in the rise of Latin American nationalism by studying Latin American book works on sports culture [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Stine et al developed a study on the coupling of physical culture and youth culture using Danish high school students as an example and pointed out that traditional physical culture is difficult to subtly integrate into youth culture [15]. Bocketti explored the role of the spread of sports culture in the rise of Latin American nationalism by studying Latin American book works on sports culture [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, topics included focus groups (e.g. Nielsen & Thing, 2019), analysis of sources (e.g. Bonde, 2009), discourse analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9 The pressure to perform well in sport and school, for example, can reduce the amount of personal time that student-athletes have, 10,11 and such time pressures can be especially intense when activities across the club-school spectrum are insufficiently coordinated. 2 Research in Scandinavia has shown, for example, how student-athletes often need to: coordinate the sometimes conflicting demands of their academic, sport and social lives 12 ; cope with injuries and overuse 13,14 ; navigate a variety of sometimes conflicting self-identities 15,16 ; negotiate gender norms that may, for example, restrict the development of young female student-athletes through the construction or promotion of discriminatory discourses that favour male student-athletes; 17,18 handle both their own expectations of athletic development and the expectations of others 19 and manage the pressure of social comparisons during regular evaluations (e.g. physical performance testing) or when competing for selection to sport activities.…”
mentioning
confidence: 99%